A lean framework for tooling design process in Chinese aerospace - Yang, Yafang (Cranfield University, 2012)
Lean Manufacturing (LM) has been used in production processes to help manufacturing companies maintain competitive advantages for decades. However, with the increasingly fierce competition and pressure to sustain survival and long-term growth, enterprises cannot be satisfied with just improving the performance of a single process. Therefore, adoption of lean to the whole product development processes has become a necessity. There is evidence that lean thinking and some lean manufacturing tools are able to improve Product Development (PD) processes. Thus, terms of Lean Product Development (Lean PD) and Lean Product and Process Development (Lean PPD) are becoming popular in engineering fields. In this project, the research aimed to improve the tooling design situation in Chinese aerospace by implementing lean techniques to the design process. Tooling is an indispensible part of aircraft manufacturing and assembly. The quality and development time can influence aircraft quality and delivery time. However, there is little research about the lean techniques implementation based on aircraft tooling design characteristics and there are few lean frameworks for aircraft tooling design process. Therefore, this research will be conducted to fill this gap. The research comprised four phases. In the first phase, a comprehensive literature review about lean (lean thinking and lean manufacturing), Lean PD and Lean PPD, tooling design, lean models/frameworks and the relationship between lean and organisational culture was conducted. In the second phase, data and information from three Chinese aircraft manufacturing companies (Company A, B and C) and literature were collected and analysed, aiming to discover the current lean implementation status in tooling design process and find improvement opportunities. In the third stage, a lean framework for tooling design process was synthesised. Finally, the proposed framework was validated by academic and industry experts. Finally, the research can contribute to companies which need a lean transformation. Moreover, the lean framework also could be used as a reference for research in lean and tooling design field.
Keywords: Lean manufacturing; Lean thinking; Product development; Lean PD; Lean PPD; Tooling design; Aerospace